George W. Cable and two sources of jazz - Smith, Hugh L. (International Library of African Music, 1960)
George Washington Cable, the great New Orleans novelist, was a literary figure who sought out Creole songs with a collector’s zeal and used them repeatedly in his novels; he also sang them from the lecture platform in just about every section of America and even in England. Cable showed as well an avid interest in a better known jazz source, that of slave songs, rhythms and dances. Employing the transcendent powers of observation necessary to an important novelist, he wrote of Creole and slave music in both fiction and magazine articles in such a way as to suggest, and even stress, musical qualities which were later to become of interest to jazz as inherent elements of jazz.
Keywords: Music; History; Jazz; Ethnomusicology; Songs; Creole dialects; Slave Music; African Music